Poster: Quantification of correlations between sleep spindles in EEG for patients with sleep apnea - De Souza, Rafael Toledo F. [UNESP]; Filho, Jose Luiz Rybarczyk [UNESP]; Lemke, Ney [UNESP]; Schonwald, Suzana V.; De Santa-Helena, Emerson L.; Gerhardt, Gunther J. L. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Obstructive Sleep Apnea (OSA) is a pathological condition characterized by repeated episodes of interruption in the upper airways ventilation (apnea and hipoapnea) during [1]. This pathology affects 4% of men and 2% of women of working age [1]. In electroencephalographic studies, sleep spindle is an element strongly associated to OSA and certainly the most studied graphoelement in the sleep study. Sleep spindles are oscillations defined by the appearance and disappearance of spindle waves between 12-14Hz at sequential intervals of 0.5-2 seconds. The purpose of this study was to analyze the percentage of correlations between different channels in electroencephalographic examinations in normal and (mild) OSA subjects. © 2013 IEEE.